Implementation of a Student-Developed, Service-Based Internship for Pharmacy Students - Carolyn Rath; Frank Tillman; Jessica Stickel; Madison Jones; Lori Armistead (University of Minnesota Libraries Publishing, 2019)
Purpose: This article describes the development, implementation, and impact of a student-created pharmacy internship program with aspects of service-learning, professional development, and ambulatory care pharmacy practice. Program Description: As the pharmacy profession continues to evolve, pharmacy internships present valuable opportunities for student pharmacists to explore career pathways and develop personal and professional skills. While internships in clinical and industry settings support interns' professional development, service-based internships provide additional benefits to student pharmacists by promoting cultural awareness, community engagement, and commitment to serving underserved patients. Student leaders from the Student Health Action Coalition (SHAC) at the University of North Carolina Eshelman School of Pharmacy created a service-learning, ambulatory care-focused pharmacy internship for fellow student pharmacists. Two rising third-year students were selected to participate in the internship in the summer of 2018. Over the two-month program, the interns participated in various program components including direct patient care activities, faculty-led workshops and topic discussions, and quality improvement projects. In addition to supporting the interns' academic and professional growth, this program also furthered the mission of SHAC to promote positive health outcomes for underserved populations. Summary: The SHAC Ambulatory Care in Underserved Populations Internship represents an innovative initiative by pharmacy student leaders to develop a service-focused internship for fellow student pharmacists. Participation in the internship provides unique opportunities not often available in conventional pharmacy curricula, including engagement with underserved patient populations and exploration of strategies to mitigate health disparities. Crafted by students for fellow students, this internship provides opportunities for personal and professional growth for both student developers and interns to carry into their future pharmacy careers.   Article Type: Student Project